Enhancing video self-modeling by head-swapping technique to teach hand-washing to young children with autism in inclusive classrooms - Wang, Jia-Yin; Wang, Hui-Ting; Lin, Fang Yu; Chen, Wen-Wen (Educational Technology ＆ Society, 2024)
Developing adaptive skills poses a significant challenge for children with autism spectrum disorder (ASD). Personal hygiene, including hand-washing, was particularly important during the Covid-19 pandemic. Video self-modeling (VSM) is an effective strategy for teaching adaptive skills due to its inherent individualization nature. However, the production and implementation of VSM face certain barriers. To address this issue, the present study employed an innovative approach termed iVSM, which utilizes the head-swapping technique to generate self-modeling videos. To evaluate the efficacy of iVSM in teaching hand-washing skills, a single-subject multiple probe design was employed across three preschool children with ASD. The findings indicated that all participants successfully acquired the targeted skill, with two of them achieving mastery following a single intervention session. The implications of these findings underscore the potential of this novel approach to strike a balance between individualization and feasibility, thereby enhancing the broader implementation of VSM within the context of inclusive education. Furthermore, future studies can focus on the comparative research and explore more applications.